HUMAN CAPYTAL MANAGEMENT IN TORISM MANAGEMENT AT THE GORONTALO CITY TOURISI AND CULTURE OFFICE - Tri Setiawati Maulana (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The objectives of this research are 1) To find out how Human Capital Management contributes to Tourism Management at the Gorontalo City Tourism and Culture Office. 2) To find out the determining factors of Human Capital Management in Tourism Management at the Tourism and Culture Office in Gorontalo CityThe method in this research uses a qualitative case study method with data collection techniques of observation, interviews and documentation.The research results show that 1) Contribution in the Gorontalon City Tourism and Culture Office increases regional tourism achievements, especially in regional income. Apart from that, of course the tourism sector plays a very important role because it is a social sector even though it is not a mandatory matter. Regional government, however, refers to elective affairs and the tourism sector provides a large share. Because every year the achievements in the Tourism and Culture Department are in the top 5 with the highest regional income achievements in the Gorontalo City Tourism and Culture sector. Apart from that, the skills possessed by each employee receive their own awards. 2) The determining factor is HR (Human Resources) both in terms of overall purpar and the structural apparatus as a whole, with the leadership model or leadership style on achievement and work motivation, and economic matters related to appreciation. Of course, managing a budget requires experience.